The Mediating Effects of Subjective Well-Being on the Relationship between the COVID-19 Pandemic and Withdrawal Intention among B40 University Students: A Conceptual Framework - Siti Zubaidah Mohd Ariffin; Nor Sa'adah Jamaluddin (International Business Education Journal, 2023)
Despite many studies investigating the determinants of students’ withdrawal intention, scant evidence could be found related to how COVID-19 occurrence affected the intention to drop out by university students. Furthermore, the mediating effect of students’ subjective well-being has been ignored by previous studies. Therefore, this conceptual paper proposes a framework which links the mediating effect of subjective well-being on the relationship between COVID-19 occurrence and students’ withdrawal intention from university. In addition, this paper also proposes a quantitative cross-sectional survey to verify the proposed framework. A research sample of undergraduate students from many disciplines and study areas belonging to the B40 socioeconomic group currently enrolled in both public and private institutions in Malaysia would be surveyed and data would be analyzed using PLS-SEM. The framework proposed by this study highlights a research gap in the present literature which needs to be filled to enhance the current understanding of extended effect of COVID-19 to higher education.